Multifunctional Thin Films of Vanadium Oxides for Enhanced Energy Applications - Ainabayev, Ardak (Trinity College Dublin. School of Physics. Discipline of Physics, 2024)
This thesis deals with the growth, characterisation, and application of VO2 and V2O3 thin films. Various methods were employed to prepare and analyze the VO2 and V2O3 films, aiming to explore the suitability of their properties for potential applications. A high-quality epitaxial ultrathin film M1-VO2 on c-plane Al2O3 was prepared by pulsed laser deposition. The low deposition temperature and tuning of the oxygen partial pressure during the growth process enable control over the grain size and oxygen vacancy concentration. This facilitated controlling the metal-insulator transition (MIT) parameters of the samples. It is demonstrated that the high density of grain boundaries associated with nanosized grains suppresses the thermal hysteresis of MIT. Simultaneous control over the density of oxygen vacancies and the size of grains enables the adjustment of the temperature coefficient of resistance, room temperature resistivity, MIT temperature, sharpness, and thermal hysteresis toward suitable values for the fabrication of efficient VO2-based uncooled bolometers. Compared with other VO2 fabrication methods, this approach can be viewed as a simpler alternative for VO2 fabrication with favorable properties for practical bolometer applications. It is demonstrated that simple, versatile, and easily scalable spray pyrolysis (SP) is capable of producing M1-VO2 and V2O3 thin films of various properties which is important considering the multifunctionality and wide commercial applicability of M1-VO2 and V2O3 oxides. Epitaxial M1-VO2 thin film on c-Al2O3 was deposited by SP method via direct single-step growth of M1-VO2 and via growth of V2O3 with the subsequent topotactical transformation into M1-VO2 via post-annealing. The obtained M1-VO2 films exhibit MIT properties comparable to those obtained using other more complicated growth methods such as molecular beam epitaxy (MBE), pulsed laser deposition (PLD), or magnetron sputtering. The M1-VO2 samples obtained by post-annealing V2O3 demonstrate improved surface roughness in comparison to the direct growth approach. It was found that post-annealing is better for tuning the oxygen content of M1-VO2, which can be useful for the fabrication of M1-VO2 with various MIT behaviour. It appears that oxygen concentration variation during growth changes the morphology of the deposited samples. It is proposed that directly grown M1-VO2 samples? MIT, electrical and thermoelectrical properties are influenced by the morphology rather than oxygen concentration variation. This offers the potential applicability of the M1-VO2 as near room temperature thermoelectric material due to enhanced power factor values. Further study revealed that SP-grown epitaxial V2O3 possesses p-type conductivity. The deposited p-type V2O3 has measurable mobility and high carrier concentration exhibiting excellent electrical performance for films deposited by inexpensive chemical synthesis methods. The optical transparency is on the lower side at higher thicknesses but improves at lower thicknesses. The calculated transparent conductive oxide (TCO) related figure of merit (FoM) of the p-type V2O3 thin films are highly competitive in comparison to some other PVD deposited p-type TCOs. It is proposed that the electric and optical performance of the V2O3 can be improved further by better control over growth orientation and morphology. The ability of the SP to produce high-quality epitaxial V2O3 with excellent electric and moderate optical properties can be suitable for the fabrication of an active element made of V2O3 facilitating the transport of photogenerated holes in solar cells.
APPROVED